2014
DOI: 10.1007/s40259-014-0108-z
|View full text |Cite
|
Sign up to set email alerts
|

Elosulfase Alfa: A Review of Its Use in Patients with Mucopolysaccharidosis Type IVA (Morquio A Syndrome)

Abstract: Elosulfase alfa (Vimizim(®)) is a recombinant form of the human lysosomal enzyme N-acetylgalactosamine-6-sulfatase (GALNS) that is lacking in patients with mucopolysaccharidosis type IVA (MPS IVA; Morquio A syndrome). It is the first, and currently only, disease-specific treatment option for this very rare, progressively degenerative, autosomal-recessive lysosomal storage disorder. Enzyme replacement therapy with elosulfase alfa aims to restore GALNS activity, thereby preventing the accumulation of keratan sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
7

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 32 publications
0
15
0
7
Order By: Relevance
“…However, the Tomatsu et al study only included 11 samples, and the type of ML, or clinical severity, was not indicated. We analyzed urine KS in 51 samples from ML patients with a well-defined clinical phenotype and a confirmed diagnosis of either ML II, ML II/III, or ML III (Leroy et al 2014;Lyseng-Williamson 2014). Urine KS was elevated in all samples from patients with ML II or ML II/III and the average urine KS level in these patients (fourfold increase relative to age-matched controls) was approximately the same as that in MPS IVA patients (4.7-fold increase).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the Tomatsu et al study only included 11 samples, and the type of ML, or clinical severity, was not indicated. We analyzed urine KS in 51 samples from ML patients with a well-defined clinical phenotype and a confirmed diagnosis of either ML II, ML II/III, or ML III (Leroy et al 2014;Lyseng-Williamson 2014). Urine KS was elevated in all samples from patients with ML II or ML II/III and the average urine KS level in these patients (fourfold increase relative to age-matched controls) was approximately the same as that in MPS IVA patients (4.7-fold increase).…”
Section: Discussionmentioning
confidence: 99%
“…The age of onset is often in early childhood but milder variants may present in adolescence (Mendelsohn et al 2013). Recently, enzyme replacement therapy with recombinant human N-acetyl-galactosamine-6-sulfatase (rhGALNS, elosulfase alfa) for the treatment of MPS IVA (Lyseng-Williamson 2014) has been approved by the Food and Drug Administration. Elevation of urinary KS is associated with MPS IVA and measurement of total urine glycosaminoglycans (GAGs) or qualitative GAG analysis to detect KS are commonly used clinical screening tests ).…”
Section: Introductionmentioning
confidence: 99%
“…Una vez internalizada, la actividad enzimática específica se incrementa en forma dosis-dependiente y se logra el catabolismo del queratán y condroitín sulfato. 28 Antes de los ensayos que llevaron a la aprobación final del tratamiento, este mecanismo de acción fue probado en condrocitos aislados de pacientes con MPS IV-A, en los que el nivel endógeno de GALNS era indetectable y el nivel de queratán sulfato era 11 veces mayor que el normal. Luego del tratamiento con elosulfasa alfa, los niveles enzimáticos fueron normales, el depósito de queratán sulfato disminuyó y hubo una modulación positiva de genes condrogénicos con un incremento en la expresión de colágeno II, colágeno X, agrecano y SOX9.…”
Section: Tratamientounclassified
“…Luego del tratamiento con elosulfasa alfa, los niveles enzimáticos fueron normales, el depósito de queratán sulfato disminuyó y hubo una modulación positiva de genes condrogénicos con un incremento en la expresión de colágeno II, colágeno X, agrecano y SOX9. 28 La eficacia de la elosulfasa alfa fue evaluada en un ensayo aleatorizado, doble-ciego, controlado con placebo y multinacional. 28 Este estudio incluyó un total de 176 pacientes, todos mayores de 5 años de edad, con una media de 11,9 años.…”
Section: Tratamientounclassified
See 1 more Smart Citation